Experimental and numerical study on laminar natural convection in a cavity heated from bottom due to an inclined fin - Varol, Yasin; Öztop, Hakan Fehmi; Ozgen, Filiz; Koca, Ahmet (Springer, 2012)
Natural convection heat transfer in an inclined fin attached square enclosure is studied both experimentally and numerically. Bottom wall of enclosure has higher temperature than that of top wall while vertical walls are adiabatic. Inclined fin has also adiabatic boundary conditions. Numerical solutions have been done by writing a computer code in Fortran platform and results are compared with Fluent commercial code and experimental method. Governing parameters are Rayleigh numbers (8.10(5) <= Ra <= 4 x 10(6)) and inclination angle (30 degrees <= and <= 120 degrees). The temperature measurements are done by using thermocouples distributed uniformly at the wall of the enclosure. Remarkably good agreement is obtained between the predicted results and experimental data. A correlation is also developed including all effective parameters on heat transfer and fluid flow. It was observed that heat transfer can be controlled by attaching an inclined fin onto wall.
Keywords: Square Cavity; Transfer Coefficient; Thin Fin; Enclosures; Air